Factors Affecting KWH Sales Through Public Electric Vehicle Charging Stations (Case Study: PT PLN (Persero) Unit Induk Distribusi Jakarta Raya) - Mimin Milasari; Tri Wahyu Adi; Ova Kurniawan; Willy Novananda Siregar; Muchamad Andi Barata (Transpublika Publisher, 2025)
Electric Vehicle Charging Stations (SPKLU) constitute a pivotal element in accelerating the acceptance of electric automobiles and advancing the transition toward sustainable energy within Indonesia. The objective of this paper is to discern the determinants that shape individual preferences in acquiring kilowatt-hours through SPKLU in the operational jurisdiction of PT PLN (Persero) Unit Induk Distribusi Jakarta Raya. The variables under scrutiny encompass the components of the marketing mix, namely merchandise, pricing, site, publicity, station attendants, operational procedure, and tangible manifestation. This investigation employed quantitative descriptive as well as causal approaches, with data processing executed through multiple linear regression facilitated by SPSS version 30. The findings reveal that advantageous placement, clarity of tariffs, and digitalised publicity exert a notable impact on consumers’ resolutions regarding SPKLU utilisation. This study suggests increasing the number of SPKLU in strategic locations, providing tariff information transparency through digital media, and increasing promotions through applications and social media campaigns. Further researchers can further examine the psychological, social, and behavioral components of consumers that influence the decision to use SPKLU.